Ultrasonic cavitation induced degradation of Congo red in aqueous solutions (Chemical Engineering Research Bulletin, 2010)
Ultrasonic cavitation induced degradation of Congo red in aqueous solution was investigated for a variety of operating conditions. It is found that the degradation of Congo red in aqueous solution follows pseudo-first-order reaction kinetics and the degradation rate is dependent on the initial concentration of Congo red, the temperature and pH of the aqueous medium. The effects of Fe2+ and Fenton reagent addition on the sonochemical degradation of Congo red were also investigated. The results obtained here indicate that the degradation rate of Congo red in aqueous solution was substantially accelerated by Fe2+, NaCl or Fenton reagent addition.Keywords: Degradation; Congo red; cavitation; sonochemistryDOI = 10.3329/cerb.v14i2.5899 Chemical Engineering Research Bulletin 14 (2010) 119-123